Spike desensitisation as a mechanism for high-contrast selectivity in retinal ganglion cells - Chang, Le; Ran, Yanli; Yang, Mingpo; Auferkorte, Olivia; Butz, Elisabeth; Hüser, Laura; Haverkamp, Silke; Euler, Thomas; Schubert, Timm (Frontiers in Cellular Neuroscience, 2024)
In the vertebrate retina, several dozens of parallel channels relay information about the visual world to the brain. These channels are represented by the different types of retinal ganglion cells (RGCs), whose responses are rendered selective for distinct sets of visual features by various mechanisms. These mechanisms can be roughly grouped into synaptic interactions and cell-intrinsic mechanisms, with the latter including dendritic morphology as well as ion channel complement and distribution. Here, we investigate how strongly ion channel complement can shape RGC output by comparing two mouse RGC types, the well-described ON alpha cell and a little-studied ON cell that is EGFP-labelled in the Igfbp5 mouse line and displays an unusual selectivity for stimuli with high contrast. Using patch-clamp recordings and computational modelling, we show that a higher activation threshold and a pronounced slow inactivation of the voltage-gated Na + channels contribute to the distinct contrast tuning and transient responses in ON Igfbp5 RGCs, respectively. In contrast, such a mechanism could not be observed in ON alpha cells.Using patch-clamp recordings and computational modelling, we show that in ON Igfbp5 cellsbut not in the ON alpha cellsa higher activation threshold and a pronounced slow inactivation of the voltage-gated Na + channels contribute to the distinct contrast tuning and transient responses of ON Igfbp5 RGCs, respectively. This study provides an example for the powerful role that the last stage of retinal processing can play in shaping RGC responses.In addition, RGC types differ in their expression of ion channels (Siegert et al., 2012;Rheaume et al., 2018;Tran et al., 2019) and how they are distributed across the cell (reviewed in (Van Hook et al., 2019)). This ion channel complement, in combination with the RGC's specific dendritic geometry, determines how synaptic input is integrated (Schachter et al., 2010;Poleg-Polsky and Diamond, 2011;Ran et al., 2020) and how the resulting signal is translated by the cell's spike generator into action potentials on the optic nerve (